SURVEY ON THE PREVALENCE OF STRING-LIKE PULSE AND INFLUENCING FACTORS IN TRADITIONAL MEDICINE SYNDROMES AMONG PATIENTS WITH ESSENTIAL HYPERTENSION (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the prevalence of string-like pulse and related factors in traditional medicine syndromes among patients with essential hypertension (EHT).Subject and method: A cross-sectional study was conducted on 239 EHT patients at the Traditional Medicine Hospital of Ho Chi Minh City.Results: The average age was 67,71 years, with females accounting for the majority (66,11%). The median BMI was 23,44 kg/m²; the median systolic and diastolic blood pressures were 120 mmHg and 80 mmHg, respectively. The prevalence of string-like pulse was 38,49%. The two most common traditional medicine syndromes were Liver - Kidney Yin deficiency (48,54%) and Yin deficiency with Yang hyperactivity (43,10%). String-like pulse appeared most frequently in the syndromes of Phlegm-dampness retention (75,86%), Liver fire rising (72,73%), and Liver Qi stagnation (66,67%). Factors significantly associated with the presence of string-like pulse included age (OR=1,05; 95% CI: 1,02–1,09; p=0,003), Yin deficiency with Yang hyperactivity (OR=2,44; 95% CI: 1,14–5,35; p=0,022), and Phlegm-dampness retention (OR=3,67; 95% CI: 1,18–13,19; p=0,024).Conclusion: The prevalence of string-like pulse in patients with essential hypertension was 38,49%. Age, Yin deficiency with Yang hyperactivity, and Phlegm-dampness retention were statistically significant factors associated with the presence of string-like pulse.
Keywords: essential hypertension, string-like pulse, traditional medicine.